Analisis Faktor Mahasiswa UIN Raden Mas Said Surakarta Belum Melakukan Vaksinasi - Haura Sabita Putri; Pipin Aulya (Literasi : Jurnal Kajian Keislaman Multi-Perspektif, 2021)
Covid-19 gives a major impact on behavior change in the world, especially in Indonesia. This is necessary to prevent the virus from spreading more widely and causing many victims. One of the preventions is by vaccinating all elements of society, including students. Therefore, this study aims to determine the reasons why students of UIN Raden Mas Said Surakarta have not been vaccinated. Researchers used qualitative methods with a case study approach in compiling the research. The case studies used are instrumental by emphasizing the understanding of an issue. Collecting data using semi-structured interviews. The results of this article show that there are several reasons students have not been vaccinated. Among these reasons are a doubt about the effectiveness of vaccines, not getting the right time, having a disease, trauma from post-vaccination events by the environment, unfamiliar with chemicals and doubts about foreign vaccine doses. This research is expected to contribute to educators or the government, especially those who set vaccine regulations.